Piezoelectric based vibration energy harvester with tip attraction magnetic force: modeling and simulation - Ibrahim , Dauda Sh.; Abdul Muthalif, Asan Gani; Saleh, Tanveer (2014)
In recent times, vibration based energy harvesting has drawn attention of many researchers worldwide. This is due to advancement in Microelectromechanical (MEM) devices and wireless sensors with power requirements in range of microwatts-milliWatts; hence vibration energy sources have promising potentials for such demands. Thus, many attempts were made by researchers to develop different system configurations for effective utilization of vibrations that happen all around us. Cantilever beams with piezoelectric patches are used to harness kinetic energy from mechanical vibrations. This paper is aimed at studying the effect of adding a magnetic force at the tip mass, which is also a magnet with opposite pole, on power output of the energy harvester. The additional attraction force between the tip mass and the fixed magnet influences stiffness of the system, whilst tuning the natural frequency. Mathematical equation to depict the relationship between tuned natural frequency and distance between permanent magnet is derived. The lumped parameter model for the harvester with single fixed magnets aligned with magnetic tip mass is derived. MATLAB software is used to perform the simulation study on influence of the magnet on the harvester.